Oviposition by Spodoptera exigua on Nicotiana attenuata primes induced plant defence against larval herbivory. (14th July 2015) - Bandoly, Michele; Hilker, Monika; Steppuhn, Anke
Summary Plants exhibit multifarious defence traits against herbivory that are constitutively expressed or induced upon attack. Insect egg deposition often precedes impending larval attack, and several plants can increase their resistance against larvae after experiencing the oviposition by an herbivore. The nature of such oviposition‐mediated resistance remains unknown, and here we aim to determine plant traits that explain it. We test whether oviposition on a host plant can induce plant defence responses or enhance (prime) the induction of defence traits in response to larval herbivory. We exposed Nicotiana attenuata plants to oviposition by moths of a generalist herbivore, Spodoptera exigua. Its larvae suffered higher mortality, retarded development and inflicted less feeding damage on oviposition‐experienced than on oviposition‐unexperienced plants. While oviposition alone did not induce any of the examined defence traits, oviposited plants exhibited a stronger inducibility of known defence traits, i.e. caffeoylputrescine (CP) and trypsin protease inhibitors (TPIs). We found no effects of oviposition on phytohormone levels, but on the feeding‐inducible accumulation of the transcription factor NaMyb8 that is governing biosynthesis of phenylpropanoid–polyamine conjugates, including CP. Comparison of larval performance on wild‐type plants, CP‐deficient plants (silenced NaMyb8 gene), and TPI‐deficient plants (silenced NaPI gene) revealed that priming of plant resistance to larvae by prior oviposition required NaMyb8‐mediated defence traits. Our results show that plants can use insect egg deposition as a warning signal to prime their feeding‐induced defence.